2020
DOI: 10.2147/opth.s282094
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Outcomes of Four-Point Scleral Fixation of Akreos AO60 Intraocular Lens Using Gore-Tex Suture

Abstract: Background/Objective To determine the refractive outcomes after 4-point scleral fixation of the Akreos AO60 intraocular lens with Gore-Tex suture. Methods This was a single referral center, multi-surgeon, retrospective consecutive case series. A total of 63 eyes met the inclusion criteria for having received surgical implantation of the Akreos AO60 intraocular lens with Gore-Tex suture from August 2014 to December 2018. Exclusion criteria included all ocular pathology t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Fixation of the Akreos IOL with Gore-Tex sutures is a relatively new technique. Short-term studies have reported the accuracy of biometric calculation and favorable visual results with the IOL sutured between 2 and 3 mm from the limbus [ 23 , 24 ] and a similar complication rate if compared to other scleral fixation techniques [ 3 , 8 , 25 ]. Studies reported good lens stability at long-term follow-up, good visual and refractive outcomes, and not a high rate of complications [ 14 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fixation of the Akreos IOL with Gore-Tex sutures is a relatively new technique. Short-term studies have reported the accuracy of biometric calculation and favorable visual results with the IOL sutured between 2 and 3 mm from the limbus [ 23 , 24 ] and a similar complication rate if compared to other scleral fixation techniques [ 3 , 8 , 25 ]. Studies reported good lens stability at long-term follow-up, good visual and refractive outcomes, and not a high rate of complications [ 14 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…13,14 The other studies assessing alternative sutured scleral fixation methods using Gore-Tex have reported complication rates of IOL tilt up to 45%. [15][16][17] However, most studies have reported good centration of IOL and pupillary capture was resolved spontaneously. Likewise, in this study, IOL capture occurred in 30.4% of the sutured group; however, all eyes exhibited good IOL centering and spontaneous improvement, except one eye.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] Attempts to mitigate these complications with polytetrafluoroethylene (Gore-Tex) sutures have shown acceptable refractive outcomes 20 but have also introduced new complications, such as granulation tissue formation into the ciliary body and sclera, IOL opacification, eyelet fractures with subsequent IOL dislocation, persistent corneal edema, and erosion of the suture through the conjunctiva. [21][22][23][24][25] Sutureless ISHF using fibrin glue has relatively lower rates of postoperative complications; however, glue-assisted techniques generally use the formation of a scleral flap, 8 which represents substantial surgical dissection. Although both glued and sutured techniques remain important methods of intrascleral fixation, our findings suggest that the sutureless flanged ISHF technique offers equivalent outcomes while avoiding the risk for complications and increased surgical manipulation inherent to these other techniques.…”
Section: Discussionmentioning
confidence: 99%